2020
DOI: 10.3390/ijms21228492
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Expression Analysis of Udp-Glucuronosyltransferases in the Whitefly Bemisia Tabaci (Gennadius) (HemipterA: Aleyrodidae)

Abstract: Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae) is an important agricultural pest worldwide. Uridine diphosphate (UDP)-glucuronosyltransferases (UGTs) are one of the largest and most ubiquitous groups of proteins. Because of their role in detoxification, insect UGTs are attracting increasing attention. In this study, we identified and analyzed UGT genes in B. tabaci MEAM1 to investigate their potential roles in host adaptation and reproductive capacity. Based on phylogenetic and structural analyses, we ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 60 publications
1
6
0
Order By: Relevance
“…Phylogenetic analysis showed a significant expansion of the BdUGT429 gene family in B. dorsalis , which was clustered into a single branch. The phenomenon of gene expansion has been reported in previous studies, such as the UGT344 family of Acyrthosiphon pisum and A. gossypii , the UGT201 family of T. urticae , the UGT33 family of B. mori and H. armigera , and the UGT352 and UGT353 families of B. tabaci 21,39–41 . The unique gene family of UGT50 has only one member, which is present in nearly all holometabolous insects.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Phylogenetic analysis showed a significant expansion of the BdUGT429 gene family in B. dorsalis , which was clustered into a single branch. The phenomenon of gene expansion has been reported in previous studies, such as the UGT344 family of Acyrthosiphon pisum and A. gossypii , the UGT201 family of T. urticae , the UGT33 family of B. mori and H. armigera , and the UGT352 and UGT353 families of B. tabaci 21,39–41 . The unique gene family of UGT50 has only one member, which is present in nearly all holometabolous insects.…”
Section: Discussionsupporting
confidence: 51%
“…The phenomenon of gene expansion has been reported in previous studies, such as the UGT344 family of Acyrthosiphon pisum and A. gossypii, the UGT201 family of T. urticae, the UGT33 family of B. mori and H. armigera, and the UGT352 and UGT353 families of B. tabaci. 21,[39][40][41] The unique gene family of UGT50 has only one member, which is present in nearly all holometabolous insects. In this study, we identified two UGT50 family members (BdUGT50B5 and BdUGT50F1) and they were clustered together with other known UGT50 genes.…”
Section: Discussionmentioning
confidence: 99%
“…and Portiera are the most prevalent endosymbionts in whitefly populations (Nogueira, 2012;Guo et al, 2023). In this study, Hamiltonella was detected in MEAM1, MED, and T. vaporariorum at frequencies of 94.3%, 81.1%, and 80%, respectively (Figure 3D).…”
Section: Hamiltonellamentioning
confidence: 49%
“…The crucial role of several UGT genes in reproduction has also been validated in insects. Knockdown of three UGT genes, namely UGT352A1 , UGT352B1 and UGT354A1 , was shown to reduce the fecundity of female Bemisia tabaci (Gennadius) ( Guo et al, 2020 ). Moreover, a recent study reported that UGT12 is a positive modulator of reproduction in brown planthopper because UGT12 knockdown resulted in a decrease in vitellogenin synthesis and hormone acid methyltransferase expression ( Ge et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%